Relationship between the Temporal Changes in Positron-Emission-Tomography-Imaging-Based Textural Features and Pathologic Response and Survival in Esophageal Cancer Patients - Yip, Stephen S. F.; Coroller, Thibaud P.; Sanford, Nina N.; Mamon, Harvey; Aerts, Hugo J. W. L.; Berbeco, Ross I. (Frontiers in Oncology, 2016)
Purpose: Although change in SUV measures and PET-based textural features during treatment have shown promise in tumor response prediction, it is unclear which quantitative measure is the most predictive. We compared the relationship between PET-based features and pathologic response and overall survival with the SUV measures in esophageal cancer. Methods: Fifty-four esophageal cancer patients received PET/CT scans before and after chemo-radiotherapy. Of these, 45 patients underwent surgery and were classified into complete, partial, and non-responders to the preoperative chemoradiation. SUVmax and SUVmean, two co-occurrence matrix (Entropy and Homogeneity), two run-length-matrix (High-gray-run-emphasis and Short-run-high-gray-run-emphasis), and two size-zone-matrix (High-gray-zone-emphasis and Short-zone-high-gray-emphasis) textures were computed. The relationship between the relative difference of each measure at different treatment time points and the pathologic response and overall survival was assessed using the area under the receiver-operating-characteristic curve (AUC) and Kaplan-Meier statistics respectively. Results: All Textures, except Homogeneity, were better related to pathologic response than SUVmax and SUVmean. Entropy was found to significantly distinguish non-responders from the complete (AUC=0.79, p=1.7x10^-4) and partial (AUC=0.71, p=0.01) responders. Non-responders can also be significantly differentiated from partial and complete responders by the change in the run length and size zone matrix textures (AUC=0.71‒0.76, p≤0.02). Homogeneity, SUVmax and SUVmean failed to differentiate between any of the responders (AUC=0.50‒0.57, p≥0.46). However, none of the measures were found to significantly distinguish between complete and partial responders with AUC<0.60 (p=0.37). Median Entropy and Run length matrix textures significantly discriminated patients with good and poor survival (log-rank p<0.02), while all other textures and survival were poorly related (log-rank p>0.25). Conclusions: For the patients studied, temporal change in Entropy and all Run length matrix were better correlated with pathological response and survival than the SUV measures. The hypothesis that these metrics can be used as clinical predictors of better patient outcomes will be tested in a larger patient dataset in the future.